Examining influential elements impacting performance in sustainable manufacturing within Malaysian enterprises: a conceptual analysis - Ang, Hong Loong; Suddin Lada; Wang Kehui; Chin, Jin Bui; Li Xinyue (Penerbit Universiti Malaysia Sabah, 2024)
This study aims to examine the impact of sustainable manufacturing factors on the performance of Malaysian manufacturing enterprises. It emphasizes sustainable innovation, quality, cost efficiency, delivery, and operational flexibility. This study adopted Dynamic Capabilities theory and aims to offer beneficial insights to manufacturing enterprises in Malaysia. The primary purpose is to propose a conceptual model for sustainable manufacturing which enhances organizational performance. This study needs more empirical validation in literature, especially on dynamic capabilities, sustainable innovation and flexibility dimensionality in predicting organizational performance, since all three factors presented a strong theoretical basis for affecting organizational performance. Future studies should explore quantitative methods and alternative samples to improve generalizability of the results. This conceptual study highlights the role that sustainable innovation and flexibility play in determining organizational performance, while also illustrating the need to incorporate these factors within sustainable manufacturing methodologies. In addition, it provides manufacturing enterprise stakeholders with insights that help them reinforce their strategic narrative to the advantages of sustainable manufacturing. The study not only offers valuable insight to policy makers, industry experts and the academic community, but it also highlights the need for more empirical research to explore and examine upon these conceptual insights.